The new encyclopedia of Southern culture. - Pillsbury, Richard; Wilson, Charles Reagan; Thomas, James G., Jr; Abadie, Ann J. (University of North Carolina Press, 2006)
New Encyclopedia of Southern Culture: Volume 2: Geography.
One of a series of volumes that build upon the original 24 subject categories used in the Encyclopedia of Southern culture, originally published in 1989.
"Sponsored by The Center for the Study of Southern Culture at the University of Mississippi."
Keywords: Southern States -- Civilization -- Encyclopedias.; Southern States -- Encyclopedias.; États-Unis (Sud) -- Civilisation -- Encyclopédies.; États-Unis (Sud) -- Encyclopédies.; HISTORY -- State & Local.; Civilization; Southern States; encyclopedias.; Encyclopedias; Encyclopedias.; Encyclopédies.